Reflective Practice: Considering the Differences in Teacher Immediacy when a K-12 Teacher Transitions to Online Higher Education - Lisa Duryee (Journal of Scholarly Engagement)
Reflective practice allows for the exploration of ideas to gain new insight about something unexpected or unknown. As a former K-12 classroom teacher, I had the opportunity to transition to higher learning in an online platform, teaching adult learners. What was unexpected about this transition were the differences I noticed in immediacy between the two platforms and the types of student. Face-to-face interactions make for easy-to-build relationships, yet I did not anticipate the difficulty in achieving this type of connection in the online classroom. Using John Dewey’s educational insight as a reflective lens, I identified the following three potential reasons that could have contributed to the differences I encountered: the teacher, the learner, and the learning environment. An introspective look at each led to a conceptual exploration and a telling of my story to reflect on my experiences and how they shaped not only the problem posed, but also the ultimate outcome and discoveries along the way.